Engineering Dry Electrode Manufacturing for Sustainable Lithium-Ion Batteries - Mohamed Djihad Bouguern; Anil Kumar Madikere Raghunatha Reddy; Xia Li; Sixu Deng; Harriet Laryea; Karim Zaghib (Batteries, 2024)
The pursuit of industrializing lithium-ion batteries (LIBs) with exceptional energy density and top-tier safety features presents a substantial growth opportunity. The demand for energy storage is steadily rising, driven primarily by the growth in electric vehicles and the need for stationary energy storage systems. However, the manufacturing process of LIBs, which is crucial for these applications, still faces significant challenges in terms of both financial and environmental impacts. Our review paper comprehensively examines the dry battery electrode technology used in LIBs, which implies the use of no solvents to produce dry electrodes or coatings. In contrast, the conventional wet electrode technique includes processes for solvent recovery/drying and the mixing of solvents like N-methyl pyrrolidine (NMP). Methods that use dry films bypass the need for solvent blending and solvent evaporation processes. The advantages of dry processes include a shorter production time, reduced energy consumption, and lower equipment investment. This is because no solvent mixing or drying is required, making the production process much faster and, thus, decreasing the price. This review explores three solvent-free dry film techniques, such as extrusion, binder fibrillation, and dry spraying deposition, applied to LIB electrode coatings. Emphasizing cost-effective large-scale production, the critical methods identified are hot melting, extrusion, and binder fibrillation. This review provides a comprehensive examination of the solvent-free dry-film-making methods, detailing the underlying principles, procedures, and relevant parameters.